Risk Factor Analysis and Prediction of Para‐Aortic Lymph Node Metastases in Locally Advanced Cervical Cancer - Tinglu Wang; Jinchen Wei; Li Jiang; Lulu Huang; Tingting Huang; Shanshan Ma; Qiufeng Huang; Yong Zhang; Fang Wu (Cancer Medicine)
ABSTRACT Background and Purpose The indications of prophylactic extended‐field radiotherapy (EFRT) remain uncertain. This study aims to identify the risk factors for para‐aortic lymph node (PALN) metastases in locally advanced cervical cancer (LACC) and determine which part of patients may benefit from prophylactic EFRT. Materials and Methods Between January 2015 and July 2023, a single‐center retrospective analysis was performed on patients with stages IB3 and IIA2‐IVA cervical cancer. Lymph node involvement was assessed using positron emission tomography/computed tomography (PET/CT). Risk factors were evaluated by logistic regression. A prediction nomogram model was developed and validated. Results Among 329 patients, 64 (19.5%) had PALN metastases. Univariate analysis indicated that tumor size > 5.3 cm, tumor maximum standardized uptake value (SUVmax) > 9.8, bilateral pelvic lymph node (PLN) metastases, the number of positive PLNs ≥ 3, and T3–T4 stages were related to PALN metastases. After multivariate logistic analysis, it was found that tumor size > 5.3 cm (odds ratio [OR] = 3.129, 95% confidence interval [CI] = 1.536–6.374, p = 0.002), and the number of positive PLNs ≥ 3 (OR = 11.260, 95% CI = 3.506–36.158, p < 0.001) were independent risk factors. The C‐index of the nomogram was 0.886 (95% CI = 0.844–0.927). The calibration plot showed that the nomogram was well‐fitted. Decision curve analysis (DCA) exhibited excellent clinical utility. Conclusion Tumor size > 5.3 cm and the number of positive PLNs ≥ 3 are independent risk factors of PALN metastases. The nomogram shows pretty good accuracy, which may provide a valuable reference for guiding patients who are very likely to develop PALN metastases to receive prophylactic EFRT.